REGROUPING OF SYNTHESIS SERIES OF DERIVATIVES 2'-HYDROXYCHALCONES AND THEIR BIOLOGICAL ACTIVITY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
The article discusses the rearrangement of the synthesized series of derivatives of 2'-hydroxychalcones, the structures of new compounds in the PMR spectra are proved, and the thionization reactions are studied. As a result of the research, anti-tuberculosis activity was found.